Optimism Correlates with Problem-Focused Coping in Thesis Students: Optimisme Berkorelasi dengan Problem-Focused Coping pada Mahasiswa yang Sedang Menyusun Skripsi - Latifah, Putri Rokhmatul; Nastiti , Dwi (Journal of Islamic and Muhammadiyah Studies, 2024)
The phenomenon of low problem-focused coping among students working on their thesis highlights a gap in their ability to effectively address challenges. This correlational quantitative study aims to explore the relationship between optimism and problem-focused coping among psychology students at Muhammadiyah University, Sidoarjo. Using data from 165 students, collected through Likert scale-based measures of optimism and problem-focused coping, the study found a significant positive correlation (rho = 0.416, p < 0.001) between optimism and problem-focused coping. This suggests that higher levels of optimism correspond to higher problem-focused coping abilities. The implications of this research extend to both students and thesis supervisors, emphasizing the importance of promoting problem-focused coping strategies during thesis preparation. Additionally, the findings serve as a reference for researchers interested in further investigating problem-focused coping among thesis students. Highlight: Correlation between optimism and coping in thesis students. Assessing coping and optimism using Likert scales. Promote coping strategies for thesis students and supervisors. Keywoard: Problem-focused coping, Optimism, Thesis students, Correlation, Likert scales.